Investigation of anomalous electron transportin the discharge of the circular electron drift accelerator - Oghienko, S.A.; Bilokin’, V.I. (Вопросы атомной науки и техники, 2015)
In the stationary discharge with azimuthal electron drift in the crossed axial electric and radial magnetic fields an azimuthal plasma heterogeneity has been specially created. It is shown experimentally that the heterogeneity increase by only ≈6% can cause accelerator discharge current increasing by ≈100 % due to its electron component increase. Formula for the electron transport velocity calculation is determined. Hall parameters are calculated using this formula and the experimental data of other researches. Both Hall parameters are in good conformity with each other. В стационарном разряде с азимутальным дрейфом электронов в скрещенных осевом электрическом и радиальном магнитном полях специально создавалась азимутальная неоднородность плазмы. Было показано, что увеличение этой неоднородности на ≈ 6% может привести к росту тока разряда до ≈ 100% из-за роста его электронной компоненты. Определена формула для расчёта скорости транспортировки электронов к аноду и рассчитан параметр Холла как с использованием этой формулы, так и - результатов экспериментов других авторов. Оба параметра Холла находятся в хорошем соответствии друг с другом. У стаціонарному розряді із азимутальним дрейфом електронів у схрещених вісьовому електричному та радіальному магнітному полях спеціально створено азимутальну неоднорідність плазми. Було показано, що її збільшення на ≈ 6% може призвести до зростання розрядного струму до ≈ 100% внаслідок росту його електронної складової. Визначено формулу для розрахунку швидкості транспортування електронів до аноду та розраховано параметр Холла як з використанням цієї формули так і - результатів експериментів інших авторів. Обидва значення параметра Холла є у добрій відповідності один до одного.